Labor Exploitation and Economic Justice: Addressing Worker Rights in Indonesia’s Informal Economy (Indonesian Economic Justice Review, 2024)
This paper examines the issue of labor exploitation within Indonesia’s informal economy and the challenges of achieving economic justice for its workers. The informal economy in Indonesia, comprising sectors such as street vending, domestic work, and casual labor, provides livelihoods for a significant portion of the population. However, workers in these sectors are often excluded from formal labor protections, resulting in poor working conditions, low wages, and a lack of social benefits. The study reviews the legal and policy framework surrounding informal labor, assessing the gaps in workers' rights protection and the challenges of extending labor laws to informal work. The paper uses case studies from sectors like agriculture, domestic work, and transport to illustrate the pervasive nature of labor exploitation and its effects on economic well-being. It critically examines the limitations of current labor laws in addressing informal workers’ needs, particularly regarding minimum wage enforcement, occupational health and safety, and social security. The findings suggest that despite some legal reforms, the informal economy remains largely unregulated, and informal workers continue to face significant economic injustice. The paper concludes by proposing recommendations for improving legal protections for informal workers, including enhanced monitoring, stronger enforcement mechanisms, and the creation of specific policies that address the unique vulnerabilities of informal labor.